Two-photon polymerization 3D printing photoresist based on dynamic borate bond as well as preparation method and application of two-photon polymerization 3D printing photoresist
By introducing dynamic borate bonds into the photoresist, combining functional monomers and multifunctional acrylate monomers, the shortcomings in the mechanical properties of existing photoresists are solved, and high-precision micro-nano device manufacturing is achieved.
Patent Information
- Application Number
- CN202411704661.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
AI Technical Summary
The existing polymer photoresist has shortcomings in mechanical properties, ceramic sintering and material stress relief toughness, which is difficult to meet the high-precision needs of micro-nano device manufacturing.
A photoresist with improved mechanical properties was prepared by combining a functional monomer containing a dynamic borate bond with a multifunctional acrylate monomer and a two-photon initiator.
It significantly improves the mechanical properties of the resin, and the photoresist shows rapid curing, excellent molding effect and wide application prospects in two-photon polymerization 3D printing technology, and is suitable for the manufacturing of micro-nano functional devices and structural support materials.
Smart Images

Figure CN119505087A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer chemistry and polymers, and in particular relates to a two-photon polymerization 3D printing photoresist based on dynamic borate ester bonds and a preparation method thereof. Background Art
[0002] Additive manufacturing (AM), also known as 3D printing, represents a new type of high-speed prototyping technology that has developed rapidly in the past 30 years and is hailed as a symbol of the "third industrial revolution". It is capable of manufacturing complex three-dimensional structures from nanometers to centimeters. Especially in the creation of micro-nano devices oriented to functional requirements, AM provides multi-scale, multi-material and multi-dimensional manufacturing capabilities. However, the manufacture of micro-nano devices requires materials with sufficient precision to meet the needs of the final product. Over the past few decades, several micro-nanoscale additive manufacturing processes have been developed, such as projection micro-stereolithography, continuous liquid interface production, two-photon polymerization, electrohydrodynamic jet printing, aerosol jet deposition and micro-selective laser melting. Among them, two-photon polymerization provides the highest printing resolution, with an extreme resolution range of 10nm to 2μm, using ultrafast lasers to selectively polymerize resin photoresists to achieve submicron resolution. In addition, the scope of two-photon polymerization has been expanded to not only utilize near-infrared light, but also widely adopt visible light oscillators for 3D micro / nanolithography to overcome the optical diffraction limit. However, the current polymer photoresist strength is still insufficient in some aspects such as mechanical properties, subsequent ceramic sintering, and material stress release toughness.
[0003] Recyclable and self-healing materials have attracted widespread interest in recent years. As materials with intrinsic mechanisms are able to undergo multiple iterations of self-recovery, the research on self-healing materials has evolved from using extrinsic self-healing agents to using intrinsic dynamic covalent bonds. Intrinsic self-healing polymers rely on supramolecular interactions or reversible covalent bonds. The former include metal-ligand coordination, hydrogen bonding, π-π stacking interactions, etc., while the latter adopt Diels-Alder reactions, reversible disulfide bonds, hindered urea bonds, boron ester bonds, etc. Self-healing materials can be applied in various fields, such as the automotive and electronics industries. Self-healing electronic devices show great promise in the fields of electronic skin and intelligent robots.
[0004] Among them, the boroester bond is a thermally stable and robust dynamic covalent bond. Compared with other dynamic covalent bond systems, it can undergo associative exchange reactions in bulk polymers without the need for catalysts, rearrange the network topology, and has been widely used in various dynamic systems. Summary of the invention
[0005] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0006] In order to achieve these purposes and other advantages according to the present invention, a two-photon polymerization 3D printing photoresist based on dynamic borate bonds is provided, characterized in that it includes a functional monomer containing a dynamic borate bond, a multifunctional acrylate monomer and a two-photon initiator; the mass percentage content of the borate functional monomer is 0.1% to 100%, the percentage content of the multifunctional acrylate monomer is 0.1% to 40%, the mixing ratio of the borate functional monomer to the multifunctional acrylate monomer is 1 to 100:0 to 40, and the mass percentage content of the two-photon initiator is 0.3 to 3%.
[0007] The present invention also provides a method for preparing a two-photon polymerization 3D printing photoresist based on a dynamic borate ester bond, comprising the following steps:
[0008] Step 1: Add the diboric acid functional component and the dihydroxy olefin monomer into a single-mouth bottle, then add the solvent and the dehydrating agent, stir and react at room temperature under shading, filter under reduced pressure after the reaction is completed to remove the insoluble solid, and remove the solvent by rotary evaporation of the filtrate under shading, and finally vacuum dry overnight to obtain a functional monomer containing a dynamic borate ester bond;
[0009] Step 2: Mix the functional monomer containing a dynamic borate ester bond in step 1 and the multifunctional acrylate in a mass ratio of 1-100:0-40, heat to 75° C. and stir until uniform and free of bubbles, to obtain a two-photon polymerization printing resin;
[0010] Step 3: Mix the two-photon polymerization printing resin and the two-photon initiator in step 2 in proportion, heat to 45-75° C. in anhydrous and oxygen-free conditions, avoid light, and stir until uniform and free of bubbles, to obtain a two-photon polymerization 3D printing photoresist.
[0011] Preferably, in step 1, the diboric acid functional component is one or more of 1,4-phenyldiboric acid, 1,3-phenyldiboric acid, 2,5-thiophenediboric acid, 1,1'-ferrocenediboric acid, 4,4'-biphenyldiboric acid or 9,9'-dimethylfluorene-2,7-diboric acid.
[0012] Preferably, in step 1, the dihydroxyethylenic monomer is one or more of 2-methyl-2-propenoic acid-2,3-dihydroxypropyl ester or 3-allyloxy-1,2-propanediol, the solvent is dichloromethane or tetrahydrofuran, and the dehydrating agent is anhydrous magnesium sulfate.
[0013] Preferably, in the step 1, the amounts of the diboric acid functional component, the dihydroxyethylenic monomer, and the dehydrating agent are 1 part, 2-2.5 parts, and 6-8 parts, respectively, and the amount of the solvent is 100-300 parts.
[0014] Preferably, in step 1, the stirring speed is 100-400 rpm, the stirring time is 6-12 h, the drying temperature is 20-40° C., and the drying time is 8-16 h.
[0015] Preferably, in step 2, the multifunctional acrylate is one or more of bisphenol A propylene glycol dimethacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, polyethylene glycol diacrylate or hexanediol diacrylate.
[0016] Preferably, in step 3, the two-photon initiator and the agent are bis(4-((4-(diphenylamino)phenyl)ethynyl)phenyl)methanone, ethyl 2,4,6-trimethylbenzoylphosphonate, 4,4'-bis(dimethylamino)benzophenone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, bis(4-((10-hexyl-10H-phenothiazine-3-yl)ethynyl)phenyl ) ketone, bis(4-((9-hexyl-9H-carbazole-3-yl)ethynyl)phenyl)ketone, bis(4-((9-benzyl-9H-carbazole-3-yl)ethynyl)phenyl)ketone, 4,4'-(10-hexyl-10-H-phenothiazine-3,7-diyl)bis(acetylene-2,1-diyl)bis(N,N-diphenylaniline) or 1-hydroxycyclohexylphenyl ketone.
[0017] The present invention includes at least the following beneficial effects: dynamic borate bonds are introduced into photosensitive functional monomers, combined with cross-linked polymers, and modified functional monomers containing dynamic borate bonds are synthesized, which significantly improve the mechanical properties of the resin. At the same time, the modified mixed resin has good compatibility with a variety of photoinitiators. By mixing a variety of components, a photoresist for new additive manufacturing, which can be quickly cured and formed, and is suitable for two-photon polymerization 3D printing molding methods and has excellent mechanical properties and molding effects is prepared. The photoresist can be molded by two-photon 3D printing technology, and by designing the structure of the final material, a micro-nano structural material with excellent mechanical properties, controllable structure, and fast molding speed can be obtained, which has broad application prospects in micro-nano functional devices and structural support materials.
[0018] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is the formula for synthesizing the functional monomer containing a dynamic borate ester bond in Example 1 of the present invention;
[0020] Figure 2This is a hydrogen nuclear magnetic resonance spectrum of the functional monomer containing a dynamic borate ester bond synthesized in Example 1 of the present invention;
[0021] Figure 3 Mechanical properties test diagram of the photoresist prepared in Example 1 of the present invention after curing;
[0022] Figure 4 This is a graph showing the results of a thermogravimetric analysis of the photoresist prepared in Example 2 after curing;
[0023] Figure 5 This is a differential scanning calorimetry test result diagram of the photoresist prepared in Example 2 of the invention after curing;
[0024] Figure 6 This is a constant displacement nanoindentation test result diagram of the photoresist prepared in Example 2 of the present invention after curing;
[0025] Figure 7 This is a graph showing the results of a constant load nanoindentation test of the photoresist prepared in Example 2 of the present invention after curing;
[0026] Figure 8 It is a trend chart of the constant displacement nanoindentation and constant load nanoindentation test results after curing of the photoresist prepared in Example 2 of the present invention;
[0027] Fig. 9 This is a SEM image of a 3D printing test of the photoresist prepared in Example 3 of the present invention;
[0028] Fig.10 This is a light microscopy image of a 3D printing test of the photoresist prepared in Example 3 of the present invention;
[0029] Fig.11 is the equation for synthesizing the functional monomer containing a dynamic borate ester bond in Example 4 of the present invention;
[0030] Fig.12 This is a hydrogen nuclear magnetic resonance spectrum of the functional monomer containing a dynamic borate ester bond synthesized in Example 4 of the present invention;
[0031] Fig.13 This is a SEM image of a 3D printing test of the photoresist prepared in Example 4 of the present invention;
[0032] Fig.14 The constant displacement nanoindentation and constant load nanoindentation test results of the photoresist prepared in Example 5 of the present invention after curing are shown;
[0033] Fig.15 This is a constant displacement nanoindentation test result diagram of the photoresist prepared in Example 6 of the present invention after curing;
[0034] Fig.16This is a graph showing the results of a constant load nanoindentation test of the photoresist prepared in Example 6 of the present invention after curing;
[0035] Fig.17 This is a test diagram of the mechanical properties of the photoresist prepared in Comparative Example 1 of the present invention after curing;
[0036] Fig.18 This is a graph showing the test results of constant displacement nanoindentation and constant load nanoindentation prepared in Comparative Example 1 of the present invention;
[0037] Fig.19 It is an integrated trend diagram of the results of the nanoindentation test of Example 5 of the present invention and Comparative Example 1 (wherein 0% of pBPDBMA addition corresponds to Comparative Example 1);
[0038] Fig. 20 It is an integrated trend diagram of the results of the nanoindentation test of Example 6 of the present invention and Comparative Example 1 (wherein 0% of DMFDBMA addition corresponds to Comparative Example 1);
[0039] Fig.21 is a structural diagram of a functional monomer containing a dynamic borate ester bond synthesized in Example 5 of the present invention;
[0040] Fig. 22 1 is a structural diagram of a functional monomer containing a dynamic borate ester bond synthesized in Example 6 of the present invention. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0042] Example 1
[0043] A method for preparing a two-photon polymerization 3D printing photoresist based on dynamic borate ester bonds, comprising:
[0044] Step 1: Add 6.64 g of 1,3-phenylenediboronic acid and 11.86 mL of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester into a single-mouth bottle, add 200 mL of tetrahydrofuran (THF) solvent, stir evenly, and then add 30 g of dehydrating agent anhydrous MgSO 4, use aluminum foil to shield the single-mouth bottle from light, stir at 400 rpm for 24 hours at room temperature, filter after the reaction is completed, remove insoluble solids, take the clear transparent liquid below, and remove the solvent by rotary evaporation. The colorless, transparent, viscous liquid is the crude product. The crude product is placed in a vacuum drying oven and dried at 40°C for 12 hours to obtain a functional monomer containing a borate ester bond, 1,3-bis(4-((3-methyl-2-methylenebut-3-ene-1-yl)oxy)methyl)-1,3,2-dioxaborolan-2-yl)benzene 14.89 g, with a yield of about 89.86%, and is stored at low temperature and away from light. The synthesis equation of the product is as follows Figure 1 As shown, the H NMR spectrum is Figure 2 As shown;
[0045] Step 2: Mix the product 1,3-bis(4-((3-methyl-2-methylenebut-3-en-1-yl)oxy)methyl)-1,3,2-dioxaborolan-2-yl)benzene (mBDBMA) obtained in the previous step with the multifunctional monomer pentaerythritol triacrylate (PETA) in a mass ratio of mBDBMA:PETA=8:2, heat to 75°C and stir evenly to obtain 5g of two-photon polymerization printing resin, i.e., photoresist precursor.
[0046] Step 3: Add 0.075 g of two-photon polymerization photoinitiator TPO-L to the photoresist precursor obtained in step 2, heat to 50°C in anhydrous and oxygen-free conditions, avoid light, mix, and stir for 6 hours until the system is uniform and free of bubbles to obtain the final photoresist.
[0047] Step 4. Re-prepare photoresists according to the ratios of mBDBMA:PETA=6:4, 7:3, 9:1 and 10:0 in step 2, and transfer the photoresists obtained in each ratio in steps 1 to 4 to polytetrafluoroethylene molds respectively. Since the two-photon initiator TPO-L also has the effect of ultraviolet light initiation, the polytetrafluoroethylene mold injected with the photoresist is placed under 365nm ultraviolet light for polymerization. After 30 minutes of ultraviolet light irradiation, a completely cured dumbbell-shaped specimen is obtained, indicating that the prepared photosensitive resin has good curing effect and molding speed.
[0048] Step 5: Take 3 dumbbell splines of each type and conduct macroscopic three-point bending test with a pressing speed of 1 mm / min to test its mechanical properties. The specific test results are shown in the attached figure. Figure 3 As shown in the figure (abbreviated as PETA-mBDB, the same below), from Figure 3 It can be seen that the product obtained after curing the 3D printing photoresist prepared in this embodiment has good curing effect and molding speed, and also has high mechanical strength.
[0049] Example 2
[0050] A method for preparing a two-photon polymerization 3D printing photoresist based on dynamic borate ester bonds, comprising:
[0051] Step 1: Add 6.64 g of 1,3-phenylenediboronic acid and 11.86 mL of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester into a single-mouth bottle, add 200 mL of tetrahydrofuran (THF) solvent, stir evenly, and then add 30 g of dehydrating agent anhydrous MgSO 4 , use aluminum foil to shade the single-mouth bottle, stir at 400 rpm for 24 hours at room temperature, filter after the reaction is completed, remove insoluble solids, take the clear transparent liquid below, and remove the solvent by rotary evaporation. The colorless, transparent, viscous liquid is the crude product. The crude product is placed in a vacuum drying oven and dried at 40°C for 12 hours to obtain a functional monomer containing a borate ester bond, 1,3-bis(4-((3-methyl-2-methylenebut-3-ene-1-yl)oxy)methyl)-1,3,2-dioxaborolan-2-yl)benzene 14.89 g, with a yield of about 89.86%, and stored at low temperature and away from light.
[0052] Step 2: Mix the product 1,3-bis(4-((3-methyl-2-methylenebut-3-en-1-yl)oxy)methyl)-1,3,2-dioxaborolan-2-yl)benzene (mBDBMA) obtained in the previous step with the multifunctional monomer pentaerythritol triacrylate (PETA) in a mass ratio of mBDBMA:PETA=8:2, heat to 75°C and stir evenly to obtain 5g of two-photon polymerization printing resin, i.e., photoresist precursor.
[0053] Step 3: Add 0.075 g of two-photon polymerization photoinitiator TPO-L to the photoresist precursor obtained in step 2, heat to 50°C in anhydrous and oxygen-free conditions, avoid light, mix, and stir for 6 hours until the system is uniform and free of bubbles to obtain the final photoresist.
[0054] Step 4: pour the photoresist obtained in step 3 into a 5mm*5mm*5mm silicone mold, and place the silicone mold injected with photosensitive resin under 365nm ultraviolet light for polymerization. After irradiation with ultraviolet light for 30 minutes, a completely cured cubic photoresist is obtained.
[0055] Step 5: Prepare photoresists according to the ratios of mBDBMA:PETA=6:4, 7:3, 9:1 and 10:0 in step 2, and take about 5 mg of the cured photoresists obtained in each ratio in steps 1 to 4 for thermogravimetric analysis. The test temperature range is 25°C to 800°C, and the heating rate is 10°C / min. The test results are shown in the attached figure. Figure 4 As shown in the figure, the residual weight data of different resins obtained by thermogravimetry were statistically analyzed. Figure 4 It can be seen that the resin has a relatively stable and high solid content of about 25%, which provides preliminary support for subsequent sintering of ceramics and other directions.
[0056] Step 6: Prepare the cured photoresist again according to the method of step 1 to step 4, and mix the three ratios of mBDBMA:PETA=6:4, 9:1 and 10:0 in step 2 to obtain small samples of about 5 mg, and perform differential scanning calorimetry analysis at a test temperature range of 25°C to 300°C. The test results are shown in the attached figure. Figure 5 As shown in the figure, it can be found that after adding mBDBMA, the resin begins to have an endothermic peak at around 120°C, and begins to decompose and release heat at around 270°C. However, pure mBDBMA resin has an endothermic peak at around 230°C, and a dynamic bond exchange reaction occurs, indicating that the resin has a certain energy dissipation capacity and improves the toughness of the material.
[0057] Step 7. Prepare the cured photoresist again according to the method of steps 1 to 4, and mix the four ratios of mBDBMA:PETA=6:4, 7:3, 8:2, and 9:1 in step 2. Take one cured photoresist of each ratio and perform nanoindentation test. On the same smooth surface, two test methods of constant load and constant indentation depth are performed respectively, wherein the load set in the constant load mode is 2mN, and the indentation depth set in the constant indentation depth mode is 500nm. Each test surface is tested more than 5 times, and the test results are shown in the attached figure. Figure 6 , 7, 8, according to the data, it can be concluded that with the addition of modified monomers, the modulus and hardness of the resin first decrease and then increase. This is because with the addition of functional monomers, the double bond content decreases, and the chemical crosslinking density of the resin decreases, which makes the overall modulus decrease. However, as the amount of functional monomers added increases further, a large number of dynamic bonds that can be dynamically exchanged are generated inside the resin after curing, thereby increasing the modulus of the resin, reaching a maximum of 7GPa.
[0058] Example 3
[0059] A method for preparing a two-photon polymerization 3D printing photoresist based on dynamic borate ester bonds, comprising:
[0060] Step 1: Add 6.64 g of 1,3-phenylenediboronic acid and 11.86 mL of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester into a single-mouth bottle, add 200 mL of tetrahydrofuran (THF) solvent, stir evenly, and then add 30 g of dehydrating agent anhydrous MgSO 4, use aluminum foil to shade the single-mouth bottle, stir at 400 rpm for 24 hours at room temperature, filter after the reaction is completed, remove insoluble solids, take the clear transparent liquid below, and remove the solvent by rotary evaporation. The colorless, transparent, viscous liquid is the crude product. The crude product is placed in a vacuum drying oven and dried at 40°C for 12 hours to obtain a functional monomer containing a borate ester bond, 1,3-bis(4-((3-methyl-2-methylenebut-3-ene-1-yl)oxy)methyl)-1,3,2-dioxaborolan-2-yl)benzene 14.89 g, with a yield of about 89.86%, and stored at low temperature and away from light.
[0061] Step 2: The product 1,3-bis(4-((3-methyl-2-methylenebut-3-en-1-yl)oxy)methyl)-1,3,2-dioxaborolan-2-yl)benzene (mBDBMA) obtained in the previous step is mixed with the multifunctional monomer pentaerythritol triacrylate (PETA) in a mass ratio of mBDBMA:PETA=6:4 to obtain 5g of two-photon polymerization printing resin, i.e., photoresist precursor.
[0062] Step 3: Add 0.035 g of two-photon polymerization photoinitiator BT-TPAA to the photoresist precursor obtained in step 2, heat to 50° C. in a dark environment, mix well, and stir for 6 hours until the system is uniform and free of bubbles to obtain the final photoresist.
[0063] Step 4: Re-prepare the photoresist according to the method of step 1 to step 3, and mix them in the ratio of 9:1 and 10:0 in step 2. Perform two-photon polymerization 3D printing test on the photoresists prepared in each ratio in step 1 to step 4. The three-dimensional structure used in the test is a conventional wooden stick pile structure, and two-photon polymerization 3D printing test is performed on each resin under different laser powers and different printing speeds. The test results are shown in the attached figure. Fig. 9 , 10 shown.
[0064] Step 5: Develop the sample printed in step 4. The sample is first soaked in propylene glycol monomethyl ether acetate for 30 minutes, then transferred to isopropyl alcohol and soaked for 10 minutes. The sample is taken out and the final product is obtained after the developer is naturally dried.
[0065] according to Fig. 9 , 10 From the electron microscope photos and printed optical microscope photos shown, it can be seen that with the increase of mBDBMA content, the printing performance of the resin decreases. This is because the cross-linking degree of the resin decreases. Under the conditions of short-term rapid curing, the resin polymerization degree cannot support a pile of wooden sticks at the hundred-nanometer level. However, under high power and lower scanning speed, samples with better molding effects can be obtained.
[0066] Example 4
[0067] A method for preparing a two-photon polymerization 3D printing photoresist based on dynamic borate ester bonds, comprising:
[0068] Step 1: Add 6.65 g of 1,4-phenylenediboronic acid and 12.5 mL of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester into a single-mouth bottle, add 200 mL of solvent dichloromethane (DCM), stir evenly, and then add 32 g of dehydrating agent MgSO 4 , use aluminum foil to shade the single-mouth bottle, stir at room temperature at 400r / min for 24h, filter after the reaction, remove insoluble solids, take the clear transparent liquid below, and remove the solvent by rotary evaporation. The colorless transparent viscous liquid is the crude product. The crude product is placed in a vacuum drying oven and dried at 40°C for 12h to obtain the final product 1,4-bis(4-((3-methyl-2-methylenebut-3-ene-1-yl)oxy)methyl)-1,3,2-dioxaborolan-2-yl)benzene 14.2g, with a yield of about 85.7%, and stored at low temperature and away from light. The synthesis equation of the product is as shown in the attached figure. Fig.11 The H NMR spectrum is shown in the attached Fig.12 shown.
[0069] Step 2: The product 1,4-bis(4-((3-methyl-2-methylenebut-3-en-1-yl)oxy)methyl)-1,3,2-dioxaborolan-2-yl)benzene (pBDBMA) obtained in the previous step is mixed with the multifunctional monomer pentaerythritol triacrylate (PETA) in a mass ratio of pBDBMA:PETA=2:8 to obtain 5g of two-photon polymerization printing resin, i.e., photoresist precursor.
[0070] Step 3: Add 0.035 g of two-photon polymerization photoinitiator BT-TPAA to the photoresist precursor obtained in step 2, heat to 50° C. in a dark environment, mix well, and stir for 6 hours until the system is uniform and free of bubbles to obtain the final photoresist.
[0071] Step 4: Prepare photoresist according to the method of step 1 to step 3, and in step 2, pBDBMA:PETA is mixed according to three ratios of 1:9, 3:7, and 4:6. The photoresists prepared in each ratio in step 1 to step 4 are subjected to two-photon polymerization 3D printing test. The three-dimensional structure used in the test is a conventional wooden stick pile structure, and each resin is subjected to two-photon polymerization 3D printing test under different laser powers and different printing speeds. The test results are shown in the attached figure. Fig.13 shown.
[0072] Step 5: Develop the sample printed in step 4. The sample is first soaked in propylene glycol monomethyl ether acetate for 30 minutes, then transferred to isopropyl alcohol and soaked for 10 minutes, the sample is taken out, and the final product is obtained after the developer is naturally dried.
[0073] according to Fig.13 It can be seen from the electron microscope photos shown that the photoresists prepared in this embodiment have very excellent printing effects.
[0074] Example 5
[0075] A method for preparing a two-photon polymerization 3D printing photoresist based on dynamic borate ester bonds, comprising:
[0076] Step 1: Add 9.74 g of 4,4'-biphenyl diboronic acid and 12.4 mL of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester into a single-mouth bottle, add 200 mL of solvent dichloromethane (DCM), stir evenly, and then add 32 g of dehydrating agent MgSO 4 , use aluminum foil to shade the single-mouth bottle, stir at room temperature at 400r / min for 24h, filter after the reaction, remove insoluble solids, take the clear transparent liquid below, and remove the solvent by rotary evaporation. The colorless, transparent, viscous liquid is the crude product. The crude product was placed in a vacuum drying oven and dried at 40°C for 12h to obtain the final product ([1,1'-biphenyl]-4,4'-diylbis(1,3,2-dioxaborane-2,4-diyl))bis(methylene)bis(2-methylacrylate) (pBPDBMA) 18.14g, with a yield of about 92.22%, and stored at low temperature and away from light. The structural diagram of the product is shown in Fig.21 shown.
[0077] Step 2: The product obtained in the previous step ([1,1'-biphenyl]-4,4'-diylbis(1,3,2-dioxaborolane-2,4-diyl))bis(methylene)bis(2-methylacrylate) (pBPDBMA) is mixed with the multifunctional monomer pentaerythritol triacrylate (PETA) in a mass ratio of pBPDBMA:PETA=1:9 to obtain 5g of two-photon polymerization printing resin, i.e., a photoresist precursor.
[0078] Step 3: Add 0.075g of two-photon polymerization photoinitiator TPO-L to the photoresist precursor obtained in step 2, heat to 50°C in a dark place to mix, stir for 6h, and obtain the final photoresist after the system is uniform and free of bubbles.
[0079] Step 4: Pour the resin obtained in step 3 into a 5mm*5mm*5mm silicone mold, and place the silicone mold injected with photosensitive resin under 365nm ultraviolet light for polymerization. After 30 minutes of ultraviolet light irradiation, a completely cured cubic sample is obtained.
[0080] Step 5: Prepare the cured photoresist again according to the method of steps 1 to 4, and mix the pBPDBMA:PETA in the ratio of 1:19 and 3:17 in step 2. Take one sample block of each mass ratio in steps 1 to 5, and perform nanoindentation test. On the same smooth surface, two test methods of constant load and constant indentation depth were performed, respectively, wherein the load set in the constant load mode was 2mN, and the indentation depth set in the constant indentation depth mode was 500nm. Each test surface was tested more than 5 times, and the test results are shown in the attached figure. Fig.14 As shown, according to the data, it can be concluded that with the addition of modified monomers, the modulus and hardness of the resin gradually increase in the same proportion, reaching a maximum modulus of 6.5 GPa.
[0081] Example 6
[0082] A method for preparing a two-photon polymerization 3D printing photoresist based on dynamic borate ester bonds, comprising:
[0083] Step 1: Add 11.36 g of 9,9-dimethylfluorene-2,7-diboronic acid and 12 mL of 2-methyl-2-acrylic acid-2,3-dihydroxypropyl ester into a single-mouth bottle, add 200 mL of solvent dichloromethane (DCM), stir evenly, and then add 31 g of dehydrating agent MgSO 4 , use aluminum foil to shade the single-mouth bottle, stir at room temperature at 400r / min for 24h, filter after the reaction, remove insoluble solids, take the clear transparent liquid below, and remove the solvent by rotary evaporation. The colorless, transparent, viscous liquid is the crude product. The crude product was placed in a vacuum drying oven and dried at 40°C for 12h to obtain the final product ((9,9-dimethyl-9H-fluorene-2,7-di)bis(1,3,2-dioxaborane-2,4-di))bis(methylene)bis(2-methylacrylate) (2,7-DMFDBMA) 19.17g, with a yield of about 90.0%, and stored at low temperature and away from light. The structural diagram of the product is shown in the figure Fig. 22 shown.
[0084] Step 2: The product obtained in the previous step (9,9-dimethyl-9H-fluorene-2,7-di)bis(1,3,2-dioxaborolane-2,4-di))bis(methylene)bis(2-methylacrylate) (2,7-DMFDBMA) is mixed with a multifunctional monomer pentaerythritol triacrylate (PETA) in a mass ratio of 2,7-DMFDBMA:PETA=1:9 to obtain 5g of two-photon polymerization printing resin, i.e., a photoresist precursor.
[0085] Step 3: Add 0.075g of two-photon polymerization photoinitiator TPO-L to the photoresist precursor obtained in step 2, heat to 50°C in a dark place to mix, stir for 6h, and obtain the final photoresist after the system is uniform and free of bubbles.
[0086] Step 4: Pour the resin obtained in step 3 into a 5mm*5mm*5mm silicone mold, and place the silicone mold injected with photosensitive resin under 365nm ultraviolet light for polymerization. After 30 minutes of ultraviolet light irradiation, a completely cured cubic sample is obtained.
[0087] Step 5: Prepare the cured photoresist again according to the method of steps 1 to 4, and mix 2,7-DMFDBMA:PETA in step 2 according to four ratios of 1:19, 3:17, 1:4, and 1:3. Take one sample block of each mass ratio in steps 1 to 5, and perform nanoindentation test. On the same smooth surface, two test methods of constant load and constant indentation depth were performed, respectively, wherein the load set in the constant load mode was 2mN, and the indentation depth set in the constant indentation depth mode was 500nm. Each test surface was tested more than 5 times, and the test results are shown in the attached figure. Figure 15-16 As shown, according to the data, it can be concluded that with the addition of modified monomers, the modulus and hardness of the resin first increase and then decrease. The best performance is obtained under the condition of 2,7-DMFDBMA:PETA=3:17, reaching a modulus of 7GPa.
[0088] Comparative Example 1
[0089] The difference between this comparative example and Example 1 is that no dynamic borate bond-containing monomer (mBDBMA) is added. Step 1: Take 5 g of multifunctional monomer pentaerythritol triacrylate (PETA) as a photoresist precursor (i.e., the amount of dynamic borate bond-containing monomer is 0);
[0090] Step 2: Add 0.075 g of two-photon polymerization photoinitiator TPO-L to the photoresist precursor obtained in step 1, heat to 50° C. and mix well under light protection, stir for 6 hours, and obtain the final photoresist after the system is uniform and free of bubbles.
[0091] Step 3: Transfer the obtained photoresist to a polytetrafluoroethylene mold. Since the two-photon initiator TPO-L also has the effect of ultraviolet light initiation, the polytetrafluoroethylene mold injected with the photoresist is placed under 365nm ultraviolet light for polymerization and curing. After 30 minutes of ultraviolet light irradiation, a completely cured dumbbell-shaped specimen is obtained.
[0092] Step 4: Take 3 dumbbell splines of each type and conduct macroscopic three-point bending test with a pressing speed of 1 mm / min to test its mechanical properties. The specific test results are shown in the attached figure. Fig.17 As shown, from Fig.17 It can be seen that the mechanical properties of the photoresist prepared without adding monomers containing dynamic borate bonds are average after curing.
[0093] Step 5, prepare the cured photoresist again according to the method of step 1 to step 4, and in step 2, the two-photon initiator content is 1.5% (0.075g) of the resin mass. The cured photoresist is subjected to a nanoindentation test. On the same smooth surface, two test methods of constant load and constant penetration depth are performed respectively, wherein the load set in the constant load mode is 2mN, and the penetration depth set in the constant penetration depth mode is 500nm. Each test surface is tested more than 5 times, and the test results are shown in the attached figure. Fig.18 As shown, from Fig.18 It can be seen that the performance of the photoresist prepared without adding monomers containing dynamic borate bonds is average.
[0094] The results of the nanoindentation test of Example 5 and Comparative Example 1 are integrated into a trend graph as shown in Fig.19 As shown (where 0% pBPDBMA addition corresponds to proportion 1), according to Fig.19 It can be concluded from the data that with the addition of modified monomers, the modulus and hardness of the resin gradually increase in the same proportion, reaching a maximum modulus of 6.5 GPa.
[0095] The results of the nanoindentation test of Example 6 and Comparative Example 1 are integrated into a trend graph as shown in Fig. 20 As shown (wherein 0% of DMFDBMA addition corresponds to proportion 1), according to Fig. 20 It can be concluded from the data that with the addition of modified monomers, the modulus and hardness of the resin first increased and then decreased. The best performance was obtained under the condition of 2,7-DMFDBMA:PETA=3:17, reaching a modulus of 7 GPa.
[0096] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A two-photon polymerization 3D printing photoresist based on dynamic borate ester bonds, characterized in that: It comprises a functional monomer containing a dynamic borate bond, a multifunctional acrylate monomer and a two-photon initiator; the mass percentage content of the borate functional monomer is 0.1% to 100%, the percentage content of the multifunctional acrylate monomer is 0.1% to 40%, the mixing ratio of the borate functional monomer to the multifunctional acrylate monomer is 1 to 100:0 to 40, and the mass percentage content of the two-photon initiator is 0.3 to 3%.
2. A method for preparing a two-photon polymerization 3D printing photoresist based on dynamic borate ester bonds, characterized in that: The following steps are involved: Step 1: Add the diboric acid functional component and the dihydroxy olefin monomer into a single-mouth bottle, then add the solvent and the dehydrating agent, stir and react at room temperature under shading, filter under reduced pressure after the reaction is completed to remove the insoluble solid, and remove the solvent by rotary evaporation of the filtrate under shading, and finally vacuum dry overnight to obtain a functional monomer containing a dynamic borate ester bond; Step 2: Mix the functional monomer containing a dynamic borate ester bond in step 1 and the multifunctional acrylate in a mass ratio of 1-100:0-40, heat to 75° C. and stir until uniform and free of bubbles, to obtain a two-photon polymerization printing resin; Step 3: Mix the two-photon polymerization printing resin and the two-photon initiator in step 2 in proportion, heat to 45-75° C. in anhydrous and oxygen-free conditions, avoid light, and stir until uniform and free of bubbles, to obtain a two-photon polymerization 3D printing photoresist.
3. The method for preparing a two-photon polymerization 3D printing photoresist based on a dynamic borate ester bond according to claim 2, characterized in that: In the step 1, the diboric acid functional component is one or more of 1,4-phenyldiboric acid, 1,3-phenyldiboric acid, 2,5-thiophenediboric acid, 1,1'-ferrocene diboric acid, 4,4'-biphenyldiboric acid or 9,9'-dimethylfluorene-2,7-diboric acid.
4. The method for preparing a two-photon polymerization 3D printing photoresist based on a dynamic borate ester bond according to claim 2, characterized in that: In the step 1, the dihydroxyethylenic monomer is one or more of 2-methyl-2-propenoic acid-2,3-dihydroxypropyl ester or 3-allyloxy-1,2-propanediol, the solvent is dichloromethane or tetrahydrofuran, and the dehydrating agent is anhydrous magnesium sulfate.
5. The method for preparing a two-photon polymerization 3D printing photoresist based on a dynamic borate ester bond according to claim 2, characterized in that: In the step 1, the amounts of the diboric acid functional component, the dihydroxyethylenic monomer, and the dehydrating agent are 1 part, 2-2.5 parts, and 6-8 parts, respectively, and the solvent is 100-300 parts.
6. The method for preparing a two-photon polymerization 3D printing photoresist based on a dynamic borate ester bond according to claim 2, characterized in that: In the step 1, the stirring speed is 100-400 rpm, the stirring time is 6-12 hours, the drying temperature is 20-40° C., and the drying time is 8-16 hours.
7. The method for preparing a two-photon polymerization 3D printing photoresist based on a dynamic borate ester bond according to claim 2, characterized in that: In the step 2, the multifunctional acrylate is one or more of bisphenol A propylene glycol dimethacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, polyethylene glycol diacrylate or hexanediol diacrylate.
8. The method for preparing a two-photon polymerization 3D printing photoresist based on dynamic borate bonds according to claim 2, characterized in that: In the step 3, the two-photon initiator and the agent are one or more of bis(4-((4-(diphenylamino)phenyl)ethynyl)phenyl)methanone, ethyl 2,4,6-trimethylbenzoylphosphonate, 4,4'-bis(dimethylamino)benzophenone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, bis(4-((10-hexyl-10H-phenothiazine-3-yl)ethynyl)phenyl)methanone, bis(4-((9-hexyl-9H-carbazole-3-yl)ethynyl)phenyl)methanone, bis(4-((9-benzyl-9H-carbazole-3-yl)ethynyl)phenyl)methanone, 4,4'-(10-hexyl-10-H-phenothiazine-3,7-diyl)bis(ethynyl-2,1-diyl)bis(N,N-diphenylaniline) or 1-hydroxycyclohexylphenyl ketone.
9. An application of a two-photon polymerization 3D printing photoresist prepared by the preparation method according to any one of claims 2 to 8, characterized in that: The two-photon polymerization 3D printing photoresist is used for molding through two-photon 3D printing technology, and the structure of the final material is designed to obtain a micro-nanostructure material with excellent mechanical properties, controllable structure and fast molding speed.
Citation Information
Cited By
Precise detection method for solid content of deep ultraviolet photoresist resin solution
CN120801691A
UV-cured acrylate / dynamic borate dual-network pressure-sensitive adhesive and preparation method thereof
CN120843022A
UV-curable acrylate / dynamic borate dual-network pressure-sensitive adhesive and its preparation method
CN120843022B